Critérios para a caracterização dos embargos declaratórios como manifestamente protelatórios - Souza, João Vitor dos Santos de (2025)
The research aims to clarify and systematize criteria for classifying the motion for clarification as dilatory, based on the article 1.026, §2 of the Brazilian Civil Procedure Code (CPC/2015), with the intent of eliminating the judicial discretion and ensuring a more predictable scenario with legal certainty for the parties. This paper begins with a historical contextualization of the motion for clarification in order to understand its theoretical basis and the effects surrounding it in the civil procedural system. Subsequently, the study seeks to highlight the role and potential of the motion for clarification in the protection of constitutional guarantees applicable to civil procedural law, rescuing it from its often undervalued status. Thereafter, it is established the premise of the dilatory motion for clarification as a type of procedural offense of bad-faith litigation, as set out in article 80, section VII, subspecies that imposes the judicial duty to apply the fine provided in the §2 of Article 1,026 of the CPC. After the contextual framework, the research intents to structure the essential elements that form the basis for classifying a dilatory motion for clarification in a way to justify the imposition of the fine estabilish in the CPC/2015, through research in the legal scientific literature and, mostly, throught the analysis of 176 decisions of the Brazilian Superior Court of Justice (STJ), dated from January 2020 to January 2024. Based on this investigation, the study identifies the most commonly adopted parameters by the STJ for applying financial penalties to dilatory motions for clarification, and proposes criteria that improves the systematization of this matter, enabling the categorization of its essential elements. The methodological approach consisted in the analysis of legal scientific literature with cases judged by the Superior Court of Justice, in order to contribute to the establishment of a clear guidelines in this subject, ensuring greater consistency in the application of penalties, combating the bad-faith litigation without restricting, in an undue manner, the legitimate opposition of the motion for clarification